Linear A and Minoan : some new old questions - Perono Cacciafoco, Francesco (2020)
The aim of this paper is to provide a synthetic outline of the attempts so far produced by scholars in trying to decipher Linear A, an undeciphered Aegean writing system (dating back to the European Bronze Age), highlighting some still unanswered epistemological questions. Linear A documents (mainly clay tablets) come (predominantly) from the Mediterranean island of Crete and transcribe Minoan, an unknown language. Being the linguistic enigma behind this writing system not yet solved, new hermeneutic approaches could be able to shed some light on old Linear A's interpretative problems. The paper is structured as an agile literature review on Linear A, followed by a series of old and new methodological questions on this Aegean writing system, involving the possible connection with Ancient Greek (through Linear B, the script transcribing Mycenaean Greek and plausibly derived - partly - from Linear A), Semitic hypotheses, theoretical parallels with the Cuneiform writing system, the idea of a grammatological macro-comparison, and the possible improvement of computational approaches to the Linear A corpus.